The role of state feelings of loneliness in the situational regulation of social affiliative behavior: Exploring the regulatory relations within a multilevel framework. - Andreas Reissmann (Public Library of Science (PLoS), 2021)
Previous empirical evidence suggests that the engagement in social interactions across different everyday contexts occurs in a manner highly responsive to a person's social affiliation needs. As has been shown repeatedly, social engagement (as well as disengagement) can be predicted from earlier situational need states, implying that homeostatic principles underlie a person's social affiliative behaviors. However, little is known about the role of emotion in these regulative processes. For this reason, the present exploratory study investigated the predictive role of state feelings of loneliness in subsequent engagement in social interaction. Since loneliness is conceptually associated with both the need to reaffiliate as well as self-protecting tendencies potentially hindering engagement in social contact, the study investigated the possibility of both increases and decreases in social contacts resulting from state feelings of loneliness. Adopting an experience sampling methodology (ESM), a sample of 65 participants was recruited from a local university and was followed for 14 days. Subjects were prompted several times a day to rate their feeling states and the quantity of social interactions, using a fixed interval assessment schedule. Statistical analyses using multilevel analysis indicated that state feelings of loneliness had complex quadratic effects upon subsequent social interaction, leading to both increases and decreases in subsequent social interaction. Moreover, these effects were contingent upon previous engagement in social interaction, implying spillover effects across social contexts that are conditionally mediated by feelings of loneliness. These findings clearly imply an important, albeit complex role of state feelings of loneliness in the regulation of social affiliation, both as a predictor and a consequence of social interaction. These exploratory findings are discussed against the background of methodological and conceptual limitations, and several recommendations for future studies are made.